Regional leadership in the global system ideas, interests and strategies of regional powers - Flemes, Daniel (Routledge Ashgate, 2010)
This collection emphasizes the role of regional powers in intra-regional, interregional and global contexts, analyzing the rise of regional powers from a comparative perspective. In so doing, the book explains how these powers have power to shape regional and global politics.